1977
DOI: 10.1007/978-1-4612-5218-4_11
|View full text |Cite
|
Sign up to set email alerts
|

Towards Implementation of Successful Medical Computer Applications

Abstract: As the price/performance ratio of computers keeps going down, their use is becoming feasible for more and more medical applications. An important factor contributing to the success of such applictions is the care and time spent in the analysis, design, development, implementation and operation phases. Although much literature is available on the actual programming aspects such as structured programming or top-down design techniques for large computer applications, little is said about the human and other facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1979
1979
1979
1979

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…However If.. problems (in applying computers in the area of patient care) include failure to adequately ... communicate with the end users, involve them more in the design process and evaluate the impact of the computer application on their environment." (12) Zimmerman and Rector, in a recently published book, discuss human engineering problems in medical computer applications, contend that new systems engender natural opposition, and suggest that introduction of a system should be preceded by discussions with users. (13) Similarly, Giebink and Hurst reviewed 29 medical computer application projects and reported that "highly supportive physicians have generally been those who participated actively in the development of the system by working directly with the developers or actually leading the project."…”
Section: Design Factorsmentioning
confidence: 99%
“…However If.. problems (in applying computers in the area of patient care) include failure to adequately ... communicate with the end users, involve them more in the design process and evaluate the impact of the computer application on their environment." (12) Zimmerman and Rector, in a recently published book, discuss human engineering problems in medical computer applications, contend that new systems engender natural opposition, and suggest that introduction of a system should be preceded by discussions with users. (13) Similarly, Giebink and Hurst reviewed 29 medical computer application projects and reported that "highly supportive physicians have generally been those who participated actively in the development of the system by working directly with the developers or actually leading the project."…”
Section: Design Factorsmentioning
confidence: 99%